The Role Of Santri To Against Hoaxes The Study on the Role of Santries in spreading of Islam Rahmatan Lil Alamin on social media - Samsul AR; Hendi Sugianto; Sulhan Sulhan (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
Against hoaxes, everyone's responsibilities A hoax is part of the crime that must be fought because it is troubling the public. The Santries have an obligation to against hoaxes. Through the literacy movement, the socialists can close the gaps in the viral hoax. The role of Santri in shaping the literacy movement has enabled the community to become aware of the knowledge provided by Santri through the media. The use of the boarding school website as part of the media to actualize Santri’s ideas on the Islamic teachings that are rahmah is part of cyber jihad. In addition, announcing activities such as classical book study, congregational prayer, discussion, and so on is part of introducing to the global world that Islam is a friendly religion that can be spread through the role of students at the boarding school. This research focuses on an analysis document on social media of pesantren, where santries are the official media of pesantren in Madura.